Mechanics and transport phenomena in agarose-based hydrogels studied by compression-relaxation tests. (1st July 2017) - Caccavo, Diego; Cascone, Sara; Poto, Serena; Lamberti, Gaetano; Barba, Anna Angela
Highlights: A full model for the mechanics and transport phenomena in hydrogels is proposed. The compression-relaxation behavior of agarose hydrogels are investigated. The model was find able to reproduce all the observed behavior. The model is easily extendable to drug delivery and biomedical systems. Abstract: Hydrogels are widespread materials, used in several frontier fields, due to their peculiar behavior: they couple solvent mass transport to system mechanics, exhibiting viscoelastic and poroelastic characteristics. The full understanding of this behavior is crucial to correctly design such complex systems. In this study agarose gels has been investigated through experimental stress-relaxation tests and with the aid of a 3D poroviscoelastic model. At the investigated experimental conditions, the agarose gels samples show a prevalent viscoelastic behavior, revealing limited water transport and an increase of the stiffness as well as of the relaxation time along with the polymer concentration. The model parameters, derived from the fitting of some experimental data, have been generalized and used to purely predict the behavior of another set of gels. The stress-relaxation tests coupled with mathematical modeling demonstrated to be a powerful tool to study hydrogels' behavior.